PENINGKATAN PENGETAHUAN KESEHATAN MATA TERKAIT BAHAYA RADIASI GADGET DI SDN KRAPYAK KOTA SEMARANG - Aninda Putri; Dewi Sari Rochmayani, Makiza Ignes Juvellin, Amanda Sari, Fatwa Salsabila (JOURNAL OF COMMUNITY DEDICATION, 2023)
Background: Gadgets in the general sense are considered electronic devices with special functions for each device—for example; computers, cellphones, games, and others. When children are given gadgets, they are often so engrossed in the world of gadgets that they forget about children's basic needs, namely learning and socializing properly. Often when their parents order them, they don't want to listen and even get angry. Objective: Community service for the children of SDN Krapyak is carried out to increase knowledge of eye health and the correct use of gadgets. Method: The dedication in this case is; awareness/increasing understanding of a problem. With the implementation technique, there are 4 stages, namely: 1) pre- test, 2) lecture, 3) question and answer, and 4) evaluation. A gain normality test was carried out. Results: The results of the knowledge of PMR SDN Krapyak cadre members showed an increase between before and after receiving the material. The pre-test knowledge presentation was in the poor category, namely 15.38%, decreasing to 0% in the post-test. Meanwhile, in the good category, the pre-test percentage, which was originally 19.23%, increased in the post-test to 80.77%. Conclusion: This community service activity for elementary school children is in line with increasing knowledge about eye health and how to use gadgets correctly.